United kingdoms multinational union states in Europe and beyond, 1800-1925 - Jackson, Alvin (Oxford scholarship online, 2023)
The United Kingdom is weakening. Alvin Jackson examines the UK in the light of the experience of similar union states elsewhere, offering a comparative study across the long nineteenth century and beyond, drawing conclusions which shed new light on the particular history, condition, and fate of the UK.